2014
DOI: 10.1016/j.tsf.2013.06.073
|View full text |Cite
|
Sign up to set email alerts
|

Active layer analysis of interpenetrating heterojunction organic thin-film solar cells by X-ray photoelectron spectroscopy

Abstract: The active layer analysis of interpenetrating heterojunction organic thin-film solar cells by X-ray photoelectron spectroscopy (XPS) has been studied. The interpenetrating heterojunction structure based on poly(3-hexylthiophene) (P3HT) and fullerene (C 60) could be fabricated by spin-coating P3HT onto a deposited C 60 film. The composition ratios of P3HT and C 60 in the interpenetrating heterojunction active layer in the depth direction and the interface morphology between the P3HT and C 60 layers have been cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The PCBM film does not show any XRD information, and the rest three films all display two XRD peaks, which are from P3HT 25 (seen in Figure S2 ). We also analyzed the concentration-depth profile of the PIN film at the vertical direction (perpendicular to the surface) by using a well-established technique (slowly etching the prepared film from the surface accompanied with XPS measurement) 26 . The chemical composition of the pristine P3HT film and the pristine PCBM film were first analyzed via XPS in order to facilitate the calculation of the P3HT and PCBM composition in the PIN film along the vertical direction.…”
mentioning
confidence: 99%
“…The PCBM film does not show any XRD information, and the rest three films all display two XRD peaks, which are from P3HT 25 (seen in Figure S2 ). We also analyzed the concentration-depth profile of the PIN film at the vertical direction (perpendicular to the surface) by using a well-established technique (slowly etching the prepared film from the surface accompanied with XPS measurement) 26 . The chemical composition of the pristine P3HT film and the pristine PCBM film were first analyzed via XPS in order to facilitate the calculation of the P3HT and PCBM composition in the PIN film along the vertical direction.…”
mentioning
confidence: 99%
“…XPS is a surface sensitive tool with the probing depth of $6 nm to 8 nm for determining the elemental composition [22,24]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, various techniques [21][22][23][24] have been employed to optimize the vertical phase separation in poly (3-hexythiophene) (P3HT): [6,6]-phenyl-C 61 -butyric acid methyl ester (PCBM) BHJ based OSCs. It was demonstrated that vapor or thermal annealing resulted in an increase of P3HT concentration at the blend/anode interface [21].…”
Section: Introductionmentioning
confidence: 99%
“…In order to further conrm the bilayer structure, the concentration-depth prole of the bilayer lm was studied by a widely used technique (slowly etching the prepared lm from the surface accompanied by XPS measurement). 25 The chemical composition of the pristine CF and PCBM lms were rst analyzed via XPS in order to facilitate the calculation of the CF and PCBM composition in the bilayer lm along the vertical direction from the surface. Fig.…”
Section: Resultsmentioning
confidence: 99%